2017
DOI: 10.1002/dac.3361
|View full text |Cite
|
Sign up to set email alerts
|

A secure authentication and key agreement scheme for roaming service with user anonymity

Abstract: Nowadays, with the advancement of wireless technologies, global mobility networks offer roaming services for mobile users. Since in global mobility networks the communication channel is public, adversaries can launch different security attacks to breach the security and privacy of data and mobile users. Hence, an authentication and key agreement scheme can be used to provide secure roaming services. It is well known that the conventional authentication schemes are not suitable for global mobility networks, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…However, Xie et al have taken the advantage of the chaotic map‐based Diffie‐Hellman problem for the key establishment. Despite the nice contributions of the papers, after careful consideration, we found that the presented authentication and key agreement protocols in all of these four are susceptible to the known session‐specific temporary information attack, and in case of the ephemeral secret leakage, the session key is revealed to adversary.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, Xie et al have taken the advantage of the chaotic map‐based Diffie‐Hellman problem for the key establishment. Despite the nice contributions of the papers, after careful consideration, we found that the presented authentication and key agreement protocols in all of these four are susceptible to the known session‐specific temporary information attack, and in case of the ephemeral secret leakage, the session key is revealed to adversary.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, to fix the issues of the scheme of Farash et al, they proposed an enhanced authentication scheme. Nevertheless, quite recently, Arshad and Rasoolzadegan have indicated the susceptibility of the presented scheme in the study of Karuppiah et al against the off‐line password‐guessing attack and the perfect forward insecurity. At the same year, Gope and Hwang evaluated the security of the suggested authentication scheme by He et al and claimed that their scheme cannot withstand the forgery attack and has unfair key agreement.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations